2020
DOI: 10.3390/ijms21113785
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Oxygen Evolution Reaction at Strontium Palladium Perovskite Electrocatalyst in Acidic Medium

Abstract: The catalytic activity of Sr2PdO3, prepared through the sol-gel citrate-combustion method for the oxygen evolution reaction (OER) in a 0.1 M HClO4 solution, was investigated. The electrocatalytic activity of Sr2PdO3 toward OER was assessed via the anodic potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The glassy carbon modified Sr2PdO3 (GC/Sr2PdO3) electrode exhibited a higher electrocatalytic activity, by about 50 times, in comparison to the unmodified electrode. The order of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 63 publications
0
4
2
Order By: Relevance
“…Figure S35). This is notably lower than values reported for other OER catalysts operating at low pH, [83][84] and probably reflects the increasing instability of this material at elevated temperatures as discussed below.…”
Section: Theoretical Insights Into the Improved Stability Of The Co-scontrasting
confidence: 55%
“…Figure S35). This is notably lower than values reported for other OER catalysts operating at low pH, [83][84] and probably reflects the increasing instability of this material at elevated temperatures as discussed below.…”
Section: Theoretical Insights Into the Improved Stability Of The Co-scontrasting
confidence: 55%
“…The apparent activation energy of the OER at an IR-corrected overpotential of 0.6 V approximated from the backward potentiodynamic scans for [Mn+Sb]Oy is ca 20 ± 10 kJ mol -1 (Figure S35). This is notably lower than values reported for other OER catalysts operating at low pH, [83][84] and probably reflects the increasing instability of this material at elevated temperatures as discussed below.…”
Section: Theoretical Insights Into the Improved Stability Of The Co-scontrasting
confidence: 55%
“…Strontium palladium perovskite Sr 2 PdO 3 when synthesized via citrate-combustion methodology portrayed excellent operation stability with the self-activation property and thus is employed as efficient electrocatalyst for OER as well as HER thus encouraging its use in fuel cells with water splitting application, where the catalyst remained stable for 3 h for OER activity. 125 Mengran Li et al 126 reported that doping of Sr + into A-site of the La(Ni,Fe)O 3− δ optimizes the electronic structure, tunes the crystalline structure and enhance the number of OER active sites on the surfaces such as hydroxylation, oxygen vacancy defects, or transition metal ions with higher valences for Co or Fe-based perovskite OER catalysts. Excellent OER is achieved on the substitution of La 3+ with Sr 2+ by improving number of Ni III OER active species, elevating Ni/Fe surface ratio and increasing O 2 2− /O − oxygen species.…”
Section: Periodic Classification Of Metal Electrocatalysts Of Electro...mentioning
confidence: 99%